Water Quality of Panchor Hot Spring in Serian, Sarawak - Diyanah, binti Ismail (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Panchor Hot Spring is a small-scale developed natural forming hot spring that located in Kampung Panchor Dayak, Serian. It is essential to study the water quality of the Panchor Hot Spring so that the public health and safety can be ensured. Water quality study was conducted from December 2013 to March at the Panchor Hot Spring based on the National Water Quality Standards. Six sampling sites were chosen from the hot spring pools as well as the drainage nearby. Results of the study showed that the water temperature ranged from 38.4 – 42 ⁰C. Generally, the temperature was lowered in January 2014 than in December 2013 and March 2014. The pH values in all sampling months ranged from 6.49 – 7.44. The conductivity did not vary throughout the sampling months, ranging between 157.83 – 195.23 µS/cm. The water velocity of the hot spring water was between 1 – 4 cm/min. The DO ranged in between 0.17 – 7.31 mg/L and the amount of TSS in the water column was 3.33 – 10 mg/L. BOD5 ranged in between 3.34 – 4.34 mg/L and COD between 6.67 – 11.67 mg/L. Three types of nutrients were analysed during this study i.e orthophosphate (0.05 – 0.11 mg/L), nitrate (0.02 – 0.09 mg/L), and ammonia (0.02 – 0.14 mg/L). By referring to NWQS, the water quality of Panchor Hot Spring is classified as clean and safe.